(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the profound impact of modern technologies on scientific research, highlighting their role in enhancing efficiency, precision, and collaboration. It discusses the evolution of technology in research, from manual tools to AI-driven systems, and explores key applications such as big data analytics, artificial intelligence, virtual simulations, and robotics. Case studies in medicine, climate research, and space exploration illustrate their transformative effects. The article also addresses interdisciplinary integration, future trends like quantum computing and digital twins, and the economic and social implications of technology-driven research. Challenges such as accessibility, ethical concerns, and the need for technical expertise are analyzed, with recommendations for bridging the digital divide and fostering global collaboration. This comprehensive overview emphasizes the indispensable role of modern technologies in shaping the future of scientific inquiry.